2005
DOI: 10.1111/j.1528-1167.2005.65204.x
|View full text |Cite
|
Sign up to set email alerts
|

Nonfebrile Illness Seizures: A Unique Seizure Category?

Abstract: Summary:Purpose. To describe the clinical characteristics of children with a first-time nonfebrile seizure in the setting of mild illness and to test the hypothesis that these seizures are associated with illness characterized by diarrhea.Methods. This retrospective cohort study was performed in a pediatric emergency department. Patients ages 6 months to 6 years who were evaluated with first-time seizures were eligible for inclusion. Subjects were divided into three groups on the basis of symptoms accompanying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 12 publications
2
29
1
Order By: Relevance
“…However, these nonfebrile seizures may be etiologically most relevant to acute gastroenteritis infections and less genetically influenced than febrile seizures. Retrospective studies of first-time seizures occurring with mild acute illness found that diarrhea or gastroenteritis was a common feature of illness in children with first-time seizures, and was more common in children with nonfebrile seizures compared to children with febrile seizures (38%–52% vs 11%–16%, P < .001) [22, 43, 44]. …”
Section: Discussionmentioning
confidence: 99%
“…However, these nonfebrile seizures may be etiologically most relevant to acute gastroenteritis infections and less genetically influenced than febrile seizures. Retrospective studies of first-time seizures occurring with mild acute illness found that diarrhea or gastroenteritis was a common feature of illness in children with first-time seizures, and was more common in children with nonfebrile seizures compared to children with febrile seizures (38%–52% vs 11%–16%, P < .001) [22, 43, 44]. …”
Section: Discussionmentioning
confidence: 99%
“…Eighty percent of those pediatric seizure patients are diagnosed with febrile seizures, and 20% are diagnosed with afebrile seizures 48-50. Seizures of any type are usually a manifestation of a number of underlying pathologic conditions to differentiate between them, careful history taking, physical examination, and laboratory work-up are usually required.…”
Section: Febrile Seizure Evaluation and Managementmentioning
confidence: 99%
“…3,4 The low incidence of unprovoked seizures in our study patients may have resulted from our structured and detailed in-person interviews regarding patient symptoms. Seizures that occurred in children with an illness, especially those without an associated fever, may have been mis-classified as unprovoked seizures in previous studies in which medical records were used for case identification.…”
Section: Discussionmentioning
confidence: 95%
“…1,2 Reports have suggested the presence of another, distinct category of provoked seizures, nonfebrile-illness seizures (or "afebrile benign convulsions"), which are not associated with a fever but occur in the presence of other symptoms of infection. 3,4 For parents whose child has had a first-time seizure, and for the physicians who treat them, the most salient concern once the child is stabilized regards the risk of recurrence. That risk has been well defined for febrile seizures but remains poorly defined for nonfebrile-illness seizures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation